SB 206553, a putative 5-HT2C inverse agonist, attenuates methamphetamine-seeking in rats - Graves Steven M; Napier T (BMC Neuroscience, 2012)
Abstract Background Methamphetamine (meth) dependence presents a substantial socioeconomic burden. Despite the need, there is no FDA-approved pharmacotherapy for psychostimulant dependence. We consider 5-HT2C receptors as viable therapeutic targets. We recently revealed that the atypical antidepressant, mirtazapine, attenuates meth-seeking in a rodent model of human substance abuse. Mirtazapine historically has been considered to be an antagonist at 5-HT2C receptors, but more recently shown to exhibit inverse agonism at constitutively active 5-HT2C receptors. To help distinguish the roles for antagonism vs. inverse agonism, here we explored the ability of a more selective 5-HT2C inverse agonist, SB 206553 to attenuate meth-seeking behavior, and compared its effects to those obtained with 5-HT2C antagonists, SDZ Ser 082 and SB 242084. To do so, rats were trained to self-administer meth and tested for seeking-like behavior in cue reactivity sessions consisting of contingently presenting meth-associated cues without meth reinforcement. We also explored motor function to determine the influence of SB 206553 and SDZ Ser 082 on motor activity in the presence and absence of meth. Results Like mirtazapine, pretreatment with SB 206553 (1.0, 5.0, and 10.0 mg/kg), attenuated meth-seeking. In contrast, the antagonists, SDZ Ser 082 (0.1, 0.3, and 1.0 mg/kg) and SB 242084 (3.0 mg/kg) had no effect on cue reactivity (CR). SB 242084 (3.0 mg/kg) failed to attenuate the effects of 5.0 and 10 mg/kg SB 206553 on CR. Motor function was largely unaltered by the 5-HT2C ligands; however, SB 206553, at the highest dose tested (10.0 mg/kg), attenuated meth-induced rearing behavior. Conclusions The lack of effect by 5-HT2C antagonists suggests that meth-seeking and meth-evoked motor activity are independent of endogenous 5-HT acting at 5-HT2C receptors. While SB 206553 dramatically impacted meth-evoked behaviors it is unclear whether the observed effects were 5-HT2C receptor mediated. Thus, SB 206553 deserves further attention in the study of psychostimulant abuse disorders.